Does lower extremity alignment during normal stance predict lower limb kinematics and kinetics during drop landings? - Sayers, M. G. L.; Buhmann, R. L.; Collings, T. J.; Mellifont, D. B.; Stuelcken, M. C. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Static lower extremity alignment (LEA) during normal stance has been used clinically as a tool to determine the presence of known anterior cruciate ligament (ACL) risk factors during dynamic tasks. Previous work investigating the relationship between static LEA during normal stance and risk factors for ACL injury is limited by the use of imprecise methods or because it focuses on knee valgus only and no other potentially important variables. The aim of this investigation was to determine the relationships between static LEA and the corresponding LEA during drop landings.